SOCIALIZATION OF RED GUAVA TO REDUCE URIC ACID IN THE YASINAN GROUP: SOSIALISASI PEMANFAATAN JAMBU BIJI MERAH DALAM UPAYA MENURUNKAN ASAM URAT PADA KELOMPOK YASINAN - Haryanti, Bin; Sari, Yeni Kartika; Romadhon, Wimar Anugrah; Rahmawati, Anita (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Many individuals in the Yasinan group report experiencing pain in their knees and back, and they also have a history of elevated uric acid levels. Uric acid is a waste product generated from the metabolism of purines, primarily filtered by the kidneys and excreted through urine. Excess uric acid accumulation in the body, known as hyperuricemia, can lead to the formation of sharp uric acid crystals in the joints, tissues, and other organs, causing inflammation and discomfort. Objective: This community service initiative aimed to enhance the understanding of the Yasinan group in Tlogo Village, Blitar Regency, East Java, regarding the use of red guava as a non-pharmacological intervention to help reduce uric acid levels. Method: The socialization activity was carried out with thirty-three participants from the Yasinan mothers’ collective. Educational materials were delivered through informational brochures and red guava samples. An evaluative assessment was conducted via post-intervention uric acid analysis to monitor changes in uric acid levels following a seven-day intervention period. Results: The findings indicated that after seven days of red guava consumption, there was an average decrease in uric acid levels of 1.128 mg/dL among participants. Conclusion: The socialization program demonstrated that the consumption of red guava fruit for seven consecutive days may contribute to a reduction in uric acid concentrations, with an average decline of 1.128 mg/dL observed.